Polystyrene microplastics induce potential toxicity through the gut-mammary axis - Zhanhang Wang; Shiyu Wang; Shujuan Liu; Zhewei Wang; Fu Li; Qiqi Bu; Xiaopeng An (npj Science of Food)
Abstract Microplastics (MPs), as an emerging environmental pollutant, pose a grave threat to food safety and public health. However, studies on MP toxicity to organs other than the intestine remain limited, especially its link to the intestinal microbiota. To address this gap, we evaluated the potential toxicity of polystyrene (PS)-MPs to the gut and mammary glands during lactation exposure in mice. PS-MPs (~1 μm) can disrupt the intestinal barrier and cause colonic inflammation and gut microbiota dysbiosis. Moreover, they can accumulate in mammary tissue and cause inflammatory damage. Transcriptome data suggested that PS-MPs cause maternal mammary lipid metabolism disorders and ferroptosis. Fecal microbial transplant (FMT) was then performed, and it reproduced the observed leakage of the blood-milk barrier and inflammation of the mammary gland. This study demonstrated that MPs induced gut and mammary inflammation and exacerbated inflammatory damage through the gut-mammary axis. In addition, MPs caused mammary lipid disorders and ferroptosis. The findings confirmed that PS-MPs may be transported to mammalian organs other than the intestine (e.g., mammary gland) and revealed the critical role of the intestinal microbiota. These findings will provide guidance for further studies on the potential foodborne risks of MPs.